Thick Film Solid-State Molecular Sensor for Acetylene Detection Based on n-n Heterojunction Semiconductor of Nanocrystalline Tungsten Oxide - Tin Oxide Compound - Phimthong-Ngam, Dr. Yutthana; Rummachat, Trakool; Jomtarak, Dr. Rangsan (Journal of Food Health and Bioenvironmental Science, 2018)
Acetylene (C2H2) is widely used as a fuel and a raw material in many industry. Its combustion leads to explode with extreme violence in environment and safety control. A highly effective sensor for C2H2 detection is essential instrument for solving problem. Therefore, we aim to develop an effective thick film solid state molecular sensor based on n-n semiconductor heterojunction of nanocrystalline tungsten oxide-tin oxide (WO3-SnO2) compound in order to early detection of C2H2. We examine the effects of the nanostructure of sintered SnO2 solid state gas sensors and the influences of W doped SnO2 (WTO) concentration on the sensitivity and electrical properties to C2H2. The WTO gas sensor was fabricated by using the screen printing technique. The series of doped substrates with various WO3 loadings from 1-70 wt.% were tested and measured for the electrical resistances in normal atmosphere and also for the sensor response to C2H2. The results showed that with W doping by range of 0.1-0.5 wt.%, the electrical resistances of films lowered significantly. Their optimal conditions for C2H2 sensor showed the sintering temperature (ST) of 600 ํC for 6 h and the composition of 0.5 wt.% WTO at the optimum operating temperature of 300 ํC. The C2H2 sensor sensitivities were further improved from 1.792 (pure SnO2) to 2.527 through the best sensor prototype. The X-ray diffraction (XRD) study of an effective sensor revealed that SnO2 contained a cassiterite phase and WO3 contained a monoclinic phase, respectively. Scanning Electron Microscope (SEM) and Transmission Electron Microscope (TEM) investigations of the samples that sintered in air showed porous polycrystalline structures with spherical grain size ranging from 30-200 nm.